Safeguarding Abuse in Health Care - Karki Bhandari, Chanda; Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: The aim of the review is to understand the concept of abuse in health care in general and its various forms. It includes- review what is meant by healthcare and health care abuse; identify its various forms and to recognize who may be the most potential victims; find out the reasons of abuse by health care providers; and know the role of ethical guidelines and institutional policy in confronting abuse in health care. Methods: Literatures and publications on the subject were searched in order to identify research studies investigating abuse in health care that were studied, analyzed and presented. Results: Abuse in health care today is an emerging concept in need of a clear analysis and definition. At the same time, boundaries to the related concepts are not demarcated. Medical professionals and institutions are being targeted worldwide today for negligence and the medical litigation has become a huge challenge. Throughout history, health care professionals have been trusted because of their competency and caring abilities. However, the disturbing reality is that physical and psychological maltreatment of patients do occur in the health care settings throughout the world. The abuse can vary from treating someone with disrespect in a way which significantly affects the person's quality of life, to causing actual physical suffering. Differently able and dependent people are more susceptible to such abuse. Work overload, Staff burnout, lack of information and instructions were also indicated to underlie instances of abuse in health care. Conclusions: We in the healthcare facility should first accept that abuse in health care does occur and causes distress. This change needs to occur at individual, cultural and structural level. Next step will be for the staffs to be aware of abuse in health care when it happens and recognize it as such. It is always better to create a situation where we could prevent abuse from happening at health centers. Hospital personnel must implement a change in workplace culture to stop abusive behaviors wherever they occur. Each and every health care facility should be client friendly and respecting their rights. Effective ethical guidelines were needed to minimize abuse as existing ethical codes were found to be ineffective and above all there was a lack of awareness of the contents of the relevant ethical documents.